Analysis of Vasectomy as a Permanent Contraceptive for Men from the Perspective of Hadith and Islamic Law: Analisis Vasektomi Sebagai Alat Kontrasepsi Permanen Bagi Pria Dalam Perspektif Hadis Dan Hukum Islam - Azhar Nasution; Edriagus Saputra; Arwansyah bin Kirin; Siti Kholidah Marbun; Erwin Saputra Andika; Meki Johendra (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This study aims to analyze the use of vasectomy as a permanent contraceptive method for men from the perspective of Hadith and Islamic law. Vasectomy is a medical procedure that involves cutting the sperm duct to prevent fertilization. Medically, this method is considered effective in controlling birth rates; however, it carries biological and psychological consequences that require careful consideration. The research employs a qualitative method with a library research approach, utilizing primary and secondary sources such as books, classical Islamic texts, academic journals, and online databases including Scopus, ScienceDirect, Sage Journal, Dimensions, and Google Scholar. The collected data were classified and analyzed descriptively, presented in narrative form, as well as through tables and graphs to enhance understanding. The findings indicate that, from the perspective of Hadith, there is no explicit prohibition against contraception; however, the practice of ‘azl (coitus interruptus) as exemplified by the Prophet suggests that birth control should be non-permanent and carried out with mutual consent between husband and wife. From the standpoint of Islamic law, permanent vasectomy is not permissible unless it is performed for legitimate medical reasons that threaten life or health. Such action contradicts the principles of maqāṣid al-sharī‘ah, particularly ḥifẓ al-nasl (protection of lineage). Therefore, this study emphasizes that decisions regarding vasectomy should integrate medical, social, and religious considerations to ensure alignment with the overarching goal of achieving maslahah (human welfare) in Islam.